Multiple Paths to Institutional-Based Trust Production and Repair: Lessons from the Russian Bank Deposit Market. Issue 9 (September 2015) - Spicer, Andrew; Okhmatovskiy, Ilya
We propose and test the proposition that state ownership represents an important mechanism of institutional-based trust production in market development that requires analysis in its own right, particularly following periods of financial crisis when the state's role as a regulator is often viewed as ineffective or corrupt. To test the proposition that state ownership and state regulation act as distinct sources of institutional-based trust production, we examine individual choices of market participation and avoidance in Russia's market for bank deposits. To analyze the consequences of institutional-based trust, we look at individual preferences to keep savings in a private bank, in a state bank, or in cash outside of the banking system. To analyze antecedent conditions, we measure an individual's trust in political actors and government agencies. Our results support the proposition that the state produces institutional-based trust in the Russian banking system through its roles as both an owner and a regulator.